The potential anticancer effect of beta-blockers and the genetic variations involved in the interindividual difference. (January 2016) - He, Ruo-Hui; He, Yi-Jing; Tang, Yong-Jun; Zhou, Hong-Hao; McLeod, Howard L; Liu, Jie
Β-ARs are extensively spread in different tissues of our body, which could be activated by neurotransmitters norepinephrine and epinephrine to mediate physiological function and abnormal states including cancer. Recently, β-AR blockers could have significant implications in cancer therapy. But the precise molecular mechanisms are far from being fully understood. Through identifying the β-AR system signal pathways relevant to cancer, we can understand the mechanisms of β-blockers used for cancer treatment. What's more, retrospective clinical data made β-blockers jump out of the traditional field of cardiovascular disease and strengthened our confidence in cancer therapy. At last, genetic studies of β-adrenergic system offered crucial genes to analyze the effects of polymorphisms on cancer susceptibility, therapy response and prognosis of cancer patients.